2018
DOI: 10.18632/oncotarget.25576
|View full text |Cite
|
Sign up to set email alerts
|

Activating HER3 mutations in breast cancer

Abstract: Recent studies have highlighted a role of HER3 in ER and HER2-driven breast cancers. We sought to investigate the role of patient-derived HER3 mutations in ER+ and HER2+ breast cancer cells using ectopic expression of HER3 mutants. We found that HER3T355I mutant is activating with increased cell proliferation in ER+ T47D and MCF-7 breast cancer cells lacking HER2 over-expression. Immunoblotting and receptor tyrosine kinase array results indicated that T47D and MCF-7 cells expressing HER3T355I had increased p-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Indeed, the alterations found in these genes such as RYR2, NOTCH1 and DMBT1 have strong association with high tumor burden and tumorigenesis (44)(45)(46)(47), possibly resulting in a worse prognosis in lung cancer patients. Further, frequent alterations of USH2A, EGFR and ERBB3 were previously reported in association with cellular proliferation (48)(49)(50)(51). Further, we observed significant increase of copy number changes in the tumor and CTCs during disease progression.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the alterations found in these genes such as RYR2, NOTCH1 and DMBT1 have strong association with high tumor burden and tumorigenesis (44)(45)(46)(47), possibly resulting in a worse prognosis in lung cancer patients. Further, frequent alterations of USH2A, EGFR and ERBB3 were previously reported in association with cellular proliferation (48)(49)(50)(51). Further, we observed significant increase of copy number changes in the tumor and CTCs during disease progression.…”
Section: Discussionsupporting
confidence: 78%
“…The mutations in the extracellular domain might destabilize its autoinhibited conformation, thereby favouring HER3 dimerization with other members of the HER family. Several of these mutations promote ligand-independent cell survival and tumour growth both in vitro and in vivo in a HER2-dependent manner 48,49 (Fig. 2a).…”
Section: Her3mentioning
confidence: 99%
“…Moreover, among the 66 total patients of the SUMMIT trial that did not respond to Neratinib monotherapy, HER3 mutations were found in 14% of their tumors. Although additional studies are needed to evaluate whether these mutations can confer resistance to Neratinib, it has recently been demonstrated that breast cancer cell lines harboring HER3 mutations (F94L, G284R, D297Y, T355I, and E1261A) have enhanced HER2-HER3 heterodimerization that induces a gain-of-function phenotype and results in Lapatinib resistance (Mishra, et al, 2018). Furthermore, it has been recently demonstrated that the FDA-approved pan-ERBB inhibitors Afatinib and Neratinib effectively reduced the expression of mutant K-RAS proteins in several tumor types (Moll HP, et al, 2018) (Booth et al, 2018) (Booth et al, 2019), thus supporting the use of these agents to treat K-RAS mutated cancers.…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%